Development strategy of Jogja anggur agrotourism during and post-covid-19 pandemic in Bantul, Indonesia - Fivintari Francy R. (EDP Sciences, 2021)
The purposes of this study are to (1) identify the environmental factors that influence the development of Jogja Wine Agrotourism; (2) Formulating development strategies for Jogja Wine Agrotourism during the Covid-19 pandemic and also after the Covid-19 pandemic. Respondents chosen by the researchers were the managers of Agro Jogja Wines, visitors and the local community. The analytical method used is SWOT and QSPM analysis. The results of the study indicate that the internal factors that greatly influence the Jogja Wine Agrotourism are the characteristics of agrotourism, while the weakness is the presence of multiple workers. The main opportunity factor is the increasing demand, while the threat factor for Jogja Wine Agrotourism is the entry of newcomers in the same field. The agro-tourism development strategy that is the main priority based on the QSPM matrix analysis during the Covid-19 pandemic is to maintain and strengthen the characteristics of agro-tourism by providing excellent service and paying attention to health protocols in order to compete with other agro-tourism, while in the post-Covid-19 pandemic, utilizing agro-tourism characteristics. Adding fruit varieties for official certification and increasing wine production so that it can become a wine development area in DIY.